1986
DOI: 10.1128/aac.29.4.660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro and in vivo activity of the bis-triazole derivative UK 49,858 with that of amphotericin B against Histoplasma capsulatum

Abstract: The antifungal activity of UK 49,858, a difluorophenyl bis-triazole derivative, was evaluated in vitro against seven strains of Histoplasma capsulatum and in vivo in AKR and C57BL/6 murine models of histoplasmosis. UK 49,858 had a lower toxicity for AKR and C57BL/6 mice than amphotericin B did. The therapeutic index of UK 49,858 was 4.3 for AKR mice and 7.1 for C57BL/6; with amphotericin B it was 2 for both mouse strains. Given orally, UK 49,858 compared favorably with amphotericin B given intraperitoneally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
1

Year Published

1987
1987
1991
1991

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 5 publications
0
22
1
Order By: Relevance
“…injection in treating normal AKR and C57BL/6 mice infected with Histoplasma capsulatum (7). Others have reported that fluconazole was more effective than the imidazole ketoconazole in treating normal mice (12,14) and rats (12,13) infected systemically with Candida albicans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…injection in treating normal AKR and C57BL/6 mice infected with Histoplasma capsulatum (7). Others have reported that fluconazole was more effective than the imidazole ketoconazole in treating normal mice (12,14) and rats (12,13) infected systemically with Candida albicans.…”
mentioning
confidence: 99%
“…However, despite the immunosuppression, the PD50 of fluconazole was unchanged and the PD50 of amphotericin B actually decreased compared with the levels previously found in the treatment of murine histoplasmosis of nonimmunosuppressed mice (7). In the latter study (7) …”
mentioning
confidence: 99%
“…It has been shown that when complex media are used for in vitro testing of fluconazole, the MIC results may be falsely high and may not correlate with clinical efficacy (16). Complex media appear to contain substances which may inhibit fluconazole in vitro (7). Furthermore, in vitro susceptibility testing of fluconazole is troublesome and difficult to reproduce among different laboratories even when the same growth medium is used (17).…”
Section: Discussionmentioning
confidence: 99%
“…In normal rats, oral fluconazole at 10 mg/kg per day for 7 days reduced Candida colony counts in the kidneys and livers as well as amphotericin B did and was nearly as effective as amphotericin B in a 21-day treatment trial. There was no further reduction in Candida colony counts when normal rats were treated with fluconazole at 40 mg/kg twice a day for 7 days. In streptozotocin-induced diabetic rats, fluconazole at 20 mg/kg per day for either 7 or 21 days compared favorably with amphotericin B in efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation